Beban Gelombang Pada Tiang Pancang Penahan Ponton Yang Diletakan Di Depan Dinding Vertikal - Irham Adrie Hakiki; Vilda Ariviana; Ika Nur Afifah; Leo Eliasta Sembiring (JURNAL TEKNIK HIDRAULIK, 2019)
Experimental Station for Coastal  developed a pilot project of modular concrete floating structure that served as a quay at Kalibaru in North Jakarta. The structure guided by piles and placed in front of Jakarta Coastal Dyke which is a vertical wall structure. From evaluating the structure performance, it is found that the strength of the pile is an important factor for service life of the structure. To provide this, a physical model test of the floating pontoon module guided by piles was conducted at the Laboratory of Balai Litbang Pantai. The model used to determine the behavior of the structure and loads that must be hold by the pile as a seakeeping mechanism. It is done by measuring force acting on piles that caused by pontoon impact by using load cells. The pontoon loaded by regular and irregular waves. From the tests result, the recorded forces has an impuls pattern which have maximum value of 112.67 N. The load that occurs on the pile was not spread evenly on the four piles that hold the floating module. The disrepancy are around 2 – 40%.   The forces acting on piles depends on the ponton distance to the vertical wall. The forces increases along with the increases of relative distances of structure to vertical wall  to the wavelength. The presence of vertical vall caused this increase because it amplify the waves acting on the structure. The amplification effect are the greatest when the structure distrance from the wall is the multiplication factor of halves of wavelength.Keywords : physical model test, pontoon, floating quay, pile guide, impact force